The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fpsyg.2017.01875
|View full text |Cite
|
Sign up to set email alerts
|

Why Women Wear High Heels: Evolution, Lumbar Curvature, and Attractiveness

Abstract: Despite the widespread use of high-heeled footwear in both developing and modernized societies, we lack an understanding of this behavioral phenomenon at both proximate and distal levels of explanation. The current manuscript advances and tests a novel, evolutionarily anchored hypothesis for why women wear high heels, and provides convergent support for this hypothesis across multiple methods. Using a recently discovered evolved mate preference, we hypothesized that high heels influence women’s attractiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Our studies suggest that individual differences in women's responses to heeled shoes can be examined using sexual selection theories. Consistent with our prediction that a high heel is a costly signal (e.g., Saad, 2013) used to augment female attractiveness (Guéguen, 2015;Morris et al, 2013; see also Lewis et al, 2017 for recent evidence) among effective competitors for mates (Vaillancourt, 2013), attractive women were more likely to choose higher-heeled shoes under time limit than their less attractive peers were. By contrast, women's own attractiveness did not predict the proportion of lower-heeled shoes they chose under time limit, even though the two image sets were equivalent in attractiveness.…”
Section: Discussionsupporting
confidence: 83%
“…Our studies suggest that individual differences in women's responses to heeled shoes can be examined using sexual selection theories. Consistent with our prediction that a high heel is a costly signal (e.g., Saad, 2013) used to augment female attractiveness (Guéguen, 2015;Morris et al, 2013; see also Lewis et al, 2017 for recent evidence) among effective competitors for mates (Vaillancourt, 2013), attractive women were more likely to choose higher-heeled shoes under time limit than their less attractive peers were. By contrast, women's own attractiveness did not predict the proportion of lower-heeled shoes they chose under time limit, even though the two image sets were equivalent in attractiveness.…”
Section: Discussionsupporting
confidence: 83%
“…However, in the literature, high-heeled shoes were not always found as the factor that increases the forward inclination of the body, its asymmetry [11], and pelvic anteversions [15] that may lead to an uneconomic body position [8,9]. Some studies [1,9,20,106] have suggested that high heels induce a vertical integration in the sacrum, pelvic tilt and lumbar adjustment due to increased activity of the hamstring muscles to counteract the abnormal gravity line. A small to moderate effect of high-heeled shoes was observed on static and dynamic pelvic positions (sagittal pelvic tilt and axial pelvic rotation) in females habituated to the use of high-heeled footwear [4].…”
Section: Discussionmentioning
confidence: 99%
“…The perception of a woman’s physical appearance by other people (both female and male) is significantly dependent on the type of footwear she is wearing. Wearing high-heeled shoes belongs to women’s social behavior that increases the attractiveness, elegance, and even self-confidence of women [1,2]. Over 50% of women wear high-heeled shoes for 1–8 h per day, and at least one-third of women in western countries wear high-heeled shoes daily [3].…”
Section: Introductionmentioning
confidence: 99%
“…Women's dyadic sexual desire (i.e., an interest in, or a wish to engage in, sexual activity with another person, and desire for sharing and intimacy with that person) predicts their inclination to buy high-heeled rather than low-heeled shoes (Watkins & Leitch, 2020). Using high-heeled footwear modifies women's lumbar curvature and gait to be more appealing to men (Lewis et al, 2017;Morris, White, Morrison, & Fisher, 2013). Clothing, above and beyond its own signalling value, can thus be used to augment evolved physiological features in such a way as to appear more attractive to the opposite sex.…”
Section: Clothing As An Example Of Non-bodily Traitsmentioning
confidence: 99%